2016
DOI: 10.1186/s13075-016-1001-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to carbamylated α-enolase epitopes in rheumatoid arthritis also bind citrullinated epitopes and are largely indistinct from anti-citrullinated protein antibodies

Abstract: BackgroundIn addition to anti-citrullinated protein antibodies (ACPAs), antibodies targeting carbamylated (i.e., homocitrullinated) proteins (anti-CarP antibodies) have been described in rheumatoid arthritis (RA). However, the extent to which anti-CarP antibodies are truly distinct from ACPA remains unclear, and few studies have focused on specific autoantigens. Here, we examine cross-reactivity between ACPA and anti-CarP antibodies, in the context of the candidate autoantigen α-enolase.MethodsCross-reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
2
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 40 publications
1
43
2
4
Order By: Relevance
“…Given the similarity of the posttranslational modification, with the ureido functional group added to the primary amine group of a basic (lysine versus arginine) amino acid, it would not be surprising to observe that anti-CarP antibodies and ACPAs cross-react (12). However, advancement in the understanding of anti-CarP antibodies has been limited by the lack of understanding of their cross-reactivity with ACPAs.…”
mentioning
confidence: 99%
“…Given the similarity of the posttranslational modification, with the ureido functional group added to the primary amine group of a basic (lysine versus arginine) amino acid, it would not be surprising to observe that anti-CarP antibodies and ACPAs cross-react (12). However, advancement in the understanding of anti-CarP antibodies has been limited by the lack of understanding of their cross-reactivity with ACPAs.…”
mentioning
confidence: 99%
“…Interestingly, mice immunized with a carbamylated protein develop antibodies recognizing both carbamylated and acetylated (self) proteins; the same can be observed when mice are immunized with an acetylated protein . This cross‐reactivity is also detected in patients in which anti‐CarP and ACPA responses show cross‐reactivity to varying degrees . Furthermore, preliminary data illustrated that an ACPA/AAPA monoclonal antibody can be cross‐reactive, and commercially available (polyclonal) antibodies are often unable to distinguish between different citrullinated and carbamylated residues .…”
Section: Hypotheses Elucidating Mechanisms Of Autoimmunity In Ramentioning
confidence: 90%
“…148 This cross-reactivity is also detected in patients in which anti-CarP and ACPA responses show crossreactivity to varying degrees. [148][149][150] Furthermore, preliminary data illustrated that an ACPA/AAPA monoclonal antibody can be crossreactive, 151 and commercially available (polyclonal) antibodies are often unable to distinguish between different citrullinated and carbamylated residues. 152 Together, these observations hint toward a cross-reactive antibody response targeting citrullinated, carbamylated, and acetylated proteins.…”
Section: Antigens Containing Other Modifications: Ampa Conceptmentioning
confidence: 99%
“…Shi et al selected FCS because it contains many types of proteins and, thus, was considered to be suitable for screening [1]. After this study, fibrinogen, vimentin, alpha-enolase and 78-kDa glucoseregulated protein (GRP78/BIP) were identified as target antigens of anti-CarP Ab [1,3,10,[12][13][14]. However, they are also target antigens of ACPA.…”
Section: Target Antigens Of Anti-carp Abmentioning
confidence: 99%
“…Therefore, the possibility of a cross-reaction is a cause of great concern. Previous studies reported that anti-CarP Ab and ACPA are cross-reactive to some extent [9][10][11]. However, since many patients who have only anti-CarP Ab or ACPA [1], or both without showing cross-reactivity [9], they are regarded as similar but different antibodies.…”
Section: Introductionmentioning
confidence: 99%